2013
DOI: 10.1038/cr.2013.164
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin from the entorhinal cortex enables neural plasticity in the auditory cortex

Abstract: Patients with damage to the medial temporal lobe show deficits in forming new declarative memories but can still recall older memories, suggesting that the medial temporal lobe is necessary for encoding memories in the neocortex. Here, we found that cortical projection neurons in the perirhinal and entorhinal cortices were mostly immunopositive for cholecystokinin (CCK). Local infusion of CCK in the auditory cortex of anesthetized rats induced plastic changes that enabled cortical neurons to potentiate their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(85 citation statements)
references
References 63 publications
9
76
0
Order By: Relevance
“…The present study confirms and extends previous findings that neuronal activity in auditory cortex is task‐dependent (Brechmann & Scheich, ; Scheich & Brosch, ; Alho et al ., ). In agreement with previous studies we found that, during task engagement, neurons in auditory cortex responded to non‐auditory stimuli that were relevant for the task, such as light flashes and a drop of water (Brosch et al ., ; Bigelow et al ., ; Li et al ., ), that responses to auditory stimuli could differ between tasks (Hocherman et al ., ; Miller et al ., ; Otazu et al ., ), and that neuronal firing rates could slowly increase or decrease for several seconds during various phases of the tasks.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The present study confirms and extends previous findings that neuronal activity in auditory cortex is task‐dependent (Brechmann & Scheich, ; Scheich & Brosch, ; Alho et al ., ). In agreement with previous studies we found that, during task engagement, neurons in auditory cortex responded to non‐auditory stimuli that were relevant for the task, such as light flashes and a drop of water (Brosch et al ., ; Bigelow et al ., ; Li et al ., ), that responses to auditory stimuli could differ between tasks (Hocherman et al ., ; Miller et al ., ; Otazu et al ., ), and that neuronal firing rates could slowly increase or decrease for several seconds during various phases of the tasks.…”
Section: Discussionmentioning
confidence: 97%
“…water (Brosch et al, 2005;Bigelow et al, 2014;Li et al, 2014), that responses to auditory stimuli could differ between tasks (Hocherman et al, 1976;Miller et al, 1980;Otazu et al, 2009), and that neuronal firing rates could slowly increase or decrease for several seconds during various phases of the tasks. The main difference from our previous study in which monkeys had to categorise the direction of frequency steps (Brosch et al, 2011a) was that in the current study we did not find firing that was related to reward expectation and reward prediction errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we established a long-term visuoauditory associative memory in rats critically dependent on the entorhinal cortex by pairing a visual stimulus (VS) with electrical stimulation of the auditory cortex 11 .Many neurons in the entorhinal cortex contain cholecystokinin (CCK) [12][13][14] . They project to and enable long-term potentiation (LTP) in the auditory cortex by responding to a formerly ineffective sound or light stimulus after pairing with a noise-burst stimulus 15 . Infusion of a CCK antagonist into the auditory cortex prevents the formation of this visuoauditory association, similar to inactivation of the entorhinal cortex 11,15 .In this study, we aimed to confirm the formation of visuoauditory associative memory between sound and light stimuli.…”
mentioning
confidence: 99%
“…They project to and enable long-term potentiation (LTP) in the auditory cortex by responding to a formerly ineffective sound or light stimulus after pairing with a noise-burst stimulus 15 . Infusion of a CCK antagonist into the auditory cortex prevents the formation of this visuoauditory association, similar to inactivation of the entorhinal cortex 11,15 .In this study, we aimed to confirm the formation of visuoauditory associative memory between sound and light stimuli. To test our hypothesis that CCK is a memory-writing chemical for visuoauditory memory in the neocortex, we determined whether the presence of CCK allowed implantation of a memory in the cortex of anesthetized rats retrievable in a behaviorally relevant context.…”
mentioning
confidence: 99%